Google Site Training Assistance for Rich and Renewable Learning Resources for SMAN 1 Driyorejo Gresik - Sabariah, Sabariah; Rufi'i, Rufi'i; Rusmawati, Retno Danu (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
In the digital era, schools must continue improving teacher skills in dealing with technological developments. Google Sites training is one solution to develop teachers' abilities in utilizing and deepening their understanding of technology as a modern learning medium. This service aims to increase the use of Google Sites as an educational tool and create a deeper understanding of technology's potential and benefits in modern education. The service method of the training was carried out through the Participatory Action Research (PAR) approach by emphasizing the active role of participants during the training. The results of teacher service can be implemented through Google Sites as a modern and adaptive learning medium. This platform can allow teachers to create interesting teaching materials with various features, such as the use of images and flexibility in creating content anytime and anywhere. The conclusion of this training improves the quality of learning in the classroom and helps teachers prepare students to face challenges in the digital era. Overall, this training went well and positively impacted teachers' abilities to create up-to-date and effective learning media by the demands of the times.